Analisis Burnout terhadap Kinerja Karyawan Berdasarkan Systematic Literature - Djaharani Djaneta; Jupita Mawardini; Andini Amalia Putri (MAMEN: Jurnal Manajemen, 2026)
Burnout refers to a state of prolonged physical, emotional, and psychological exhaustion that may adversely influence employees’ productivity and overall job performance. This study seeks to examine the factors contributing to burnout, explore its effects on employee performance, and identify effective strategies for its prevention through a Systematic Literature Review (SLR). The study was conducted following the PRISMA 2020 framework by reviewing relevant scholarly publications indexed in Scopus and other supporting academic sources that fulfilled the established inclusion criteria. The review findings reveal that burnout is associated with several factors, including excessive workload, inadequate organizational support, leadership practices, individual attributes, and conflicts between work and personal life. Furthermore, burnout contributes to decreased productivity, lower work motivation, reduced quality of performance, and weakened organizational commitment, while simultaneously increasing absenteeism and turnover intentions. Preventive efforts can be enhanced through stronger organizational support, the implementation of work–life balance initiatives, supportive leadership, and the development of personal resources such as emotional intelligence, resilience, and self-efficacy. The results provide useful insights for organizations in designing human resource management strategies aimed at improving employee well-being and organizational effectiveness.